Supplementation of xylitol-containing chewing gum with probiotics: a double blind, randomised pilot study focusing on saliva flow and saliva properties. Issue 3 (25th February 2016) - Gueimonde, Laura; Vesterlund, Satu; García-Pola, María J.; Gueimonde, Miguel; Söderling, Eva; Salminen, Seppo
Abstract : The aim of this study was to investigate the impact of daily chewing, for 12 weeks, of 2 different probiotic gums compared with placebo on saliva flow rate, saliva IgA levels and saliva pH. Abstract : The aim of this study was to investigate the impact of daily chewing, for 12 weeks, of 2 different probiotic gums compared with placebo on saliva flow rate, saliva IgA levels and saliva pH. The intervention study included 54 adult volunteers with hyposalivation in a double-blind, randomised and placebo-controlled design with three parallel groups. Volunteers were randomly assigned to 3 different groups: subjects in group A ( n = 19) were given placebo chewing gum, group B ( n = 17) received Bifidobacterium animalis ssp. lactis Bb12 (ATCC 27536) and group C ( n = 18) received Lactobacillus rhamnosus LGG (ATCC 53103), Bifidobacterium longum 46 (DSM 14583) and Bifidobacterium longum 2C (DSM 14579) gums, during 3 months. Two volunteers from group B left the study for personal reasons leaving 19, 15 and 18 volunteers, respectively, for analyses. Clinical examinations, personal interviews, sialometries and saliva sampling were conducted at baseline and after 1, 2, 3 and 4 months. No statistically significant differences were found between probiotic and placebo groups for any of the parameters analysed. No side effects of probiotic or placebo chewing gums were observed. Chewing gum, with and without probiotics, had a positive impact on salivary flow rate and saliva pH and IgA levels.